The potential of Goniozus omanensis as an agent of biocontrol in Oman - Almandhari, Tarik Hamood Mohammed (2023)
This thesis presents a series of scientific research projects aimed to enhance the potential of Goniozus omanensis as an agent of biological pest control in Oman. The enhancements include relatively straightforward considerations, such as the formal description and scientific identification of Goniozus omanensis, as it is a new species of parasitoid wasp first recoded as the most common natural enemy on the lesser date moth, Batrachedra amydraula (LDM) in Oman in 2006. Also these enhancements include evaluating the wasp's performance for efficient mass rearing and targeted use as an agent of biological control. The first chapter provides the general background to date palm agro-ecology in Oman and the biological control of date palm pests. It discusses the importance of utilisation the parasitoid Goniozus omanensis as a biological control agent for LDM control in Oman and related technical aspects. Next, the main principles of the thesis works performed are presented. The first empirical research work (Chapter 2) is related to the scientific identification and description of the parasitoid, based on morphological description and DNA sequence data, and its registration as a new species of Bethylid wasp that is formally named Goniozus omanensis Polaszek sp. n. The second empirical project (Chapter 3) evaluates two readily-available species of Pyralid moths, Corcyra cephalonica and Galleria mellonella, as potential factitious hosts for Goniozus omanensis, with the goal of using them for mass-rearing and maintaining efficient cultures of the parasitoid throughout the year. The next project (Chapter 4) is a literature-based exploration of the date palm agro-ecosystem as an ecological community. This is achieved by extracting diet breadth records and constructing connectance trophic webs. This analysis investigates interactions between three trophic levels, between plant species with their herbivores and between these herbivores and their natural enemies, focusing on how trophic web structure might affect populations of the lesser date moth. The food webs including and excluding consideration of intercrop species are analysed. The final, empirical, project (Chapter 5) investigates effects of insecticides, specifically the botanical (plant-derived) Neem oil, on the laboratory performance of G. omanensis. Sub-lethal exposure effects of insecticides on parasitoid life-histories are often unknown and, in the field, G. omanensis, is likely to be explosed to a range of agro-chemicals. The thesis concludes that G. omanensis is a beneficial natural enemy already present in the date palm agro-ecosystem that warrants ecological attention.